Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Pada CV Musika - Yolanda Noor Lintang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
In the current rapid development of the business world, making competition between companies tighter, which requires the company to manage its business better, which in turn the company is able to compete and has superior value compared to other companies. This study aims to determine and analyze the factors that affect the performance of CV Musika employees. The population used in this study consisted of all employees of CV Musika. The number of samples in this study were 92 people with sampling techniques using total sampling. The data analysis technique uses factor analysis with the help of the SPSS 25 program. Of the 38 variables analyzed, 23 variables were obtained and 6 factors were formed that affect employee performance at CV Musika. The results of the study obtained an eigen value of 9.205 for the physical needs factor, reward factor 2.636, discipline factor 1.696, factor carrying out work procedures 1.352, work loyalty factor 1.080, attendance factor on time 1.003, so it can be concluded that these 6 factors are the most influential on employee performance at CV. Musika.